2015
DOI: 10.2460/javma.247.4.375
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding a weight loss food beyond a caloric restriction period on body composition and resistance to weight gain in dogs

Abstract: Results suggested that feeding overweight dogs the test food caused weight loss and improvements in body condition during the weight-maintenance phase, possibly because the food composition improved energy metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Clinical blood chemistry was performed on a COBAS c501 module (Roche Diagnostics Corporation, Indianapolis, IN, USA). Analysis of plasma metabolomics was performed by Metabolon (Morrisville, NC) as previously described [38,39].…”
Section: Study Design and Measurementsmentioning
confidence: 99%
“…Clinical blood chemistry was performed on a COBAS c501 module (Roche Diagnostics Corporation, Indianapolis, IN, USA). Analysis of plasma metabolomics was performed by Metabolon (Morrisville, NC) as previously described [38,39].…”
Section: Study Design and Measurementsmentioning
confidence: 99%
“…When assessed in a colony setting, weight loss protocols for obese dogs are very successful with typical rates of weight loss consistently over 1 % per week, when restricting caloric intake to 50-75 % of maintenance energy requirements (33)(34)(35)(36) . Whilst there are many advantages to performing such studies in a colony, most notably in consistency and control, the results are not necessarily representative of how obese dogs lose weight when supervised by their owners.…”
Section: Rate Of Weight Loss and Energy Intake During Weight Managementmentioning
confidence: 99%
“…the first 2-3 months) (26,29,32,36) . Such work certainly provides useful information on the early stages of a weight loss protocol, such as initial rate and initial energy intake required for weight loss.…”
Section: Likelihood Of Successfully Reaching Target Weightmentioning
confidence: 99%
“…Many of the first weight loss studies were conducted in research colony dogs, and reported universal success with rates of weight loss progressing at 1–2% per week [ 14 16 ]. Other studies have demonstrated successful weight loss in pet dogs with naturally-occurring obesity, although weight loss is slower than in the colony studies (mean <1% per week) [ 10 12 ], and many dogs fail to reach their target weight [ 11 , 17 ].…”
Section: Introductionmentioning
confidence: 99%